INNOVATION CHANGE OF TERMS’ DEFINITION IN LABOR PROTECTION SPHERE - Y. V. Baranov (Вестник СибАДИ, 2018)
Introduction. The article considers concepts in the labor protection sphere, which, by the author’s opinion, don’t take into account the current requirements of the economic development process, including such processes as the economic recovery and the growth of the living standard of the population, which could be possible only through the working person’s factor. Thus, without solving the social problems of the working group, the economic tasks would be problematic or impossible to solve. Accordingly, wages should be paid for labor, but not only for a job attendance and such approach would be one of the main instruments for economic activity management. Materials and methods. The collective-contractual regulation form of social and labor relations, including the labor protection sphere, develops nowadays at the stage of innovative economy transition. Therefore, the mutual interests of the employer and the employee in conditions’ improving and labor protection should become the basis for the development and solution of these problems. Results. In addition, the definitions of certain terms in the labor protection shere are proposed in the article. Сonclusion. It can be concluded that the term «labor protection» is determined as a social and labor relations between participants of the labor process in the safety sphere, but not as a system of organizational, technical, sanitary and other measures.